National Art Gallery, Accra - Hayford, Joseph E. (2012)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of Postgraduate Diploma in Architecture, 1986